El principio del interés superior de los niños y su desarrollo integral en los centros de privación de libertad - Asto Baque, Nicole Vanesa (2024)
ABSTRACT: In Ecuador, many inequalities persist in relation to children. Attention to the integral development of children under three years of age can be improved by promoting policies, programs and projects that help communities and institutions to identify the real dimension of the problem and deploy measures to meet the needs and basic development of infants and their families. Unfortunately, it is common to find in Ecuador cases in which the principle of the best interest of children and their integral development in the centers of deprivation of liberty, are violated; so it has been observed at present the risks they run by having mothers in these centers of deprivation and their integral development from the beginning situation that are not correct; for this reason they are losing their skills and abilities to develop in their mental, mental and personal development. Our regulations, conventions and international treaties protect each of the rights of children so that they can develop in an adequate environment for them, so it is worth mentioning that in many of these prisons there are no spaces that are suitable for children to visit their mothers, this means that they are exposed to suffer psychological damage at an early age.